Novel biodegradable composites based on PHBV: Effect of nanocellulose incorporation on the non-isothermal crystallization kinetic and structural parameters - Benini, Kelly C.C.C. [UNESP]; Ornaghi Júnior, Heitor L.; Bianchi, Otavio; de Magalhães, Welington Ferreira; Henriques, Fernando Fulgêncio; Windmoller, Dario; Voorwald, Herman J.C. [UNESP]; Cioffi, Maria O.H. [UNESP] (Wiley, 2019)
This study presents the non-isothermal behavior of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) biodegradable films with 1–5 wt% of cellulose nanoparticles (CNs) manufactured by solution casting using N,N-dimethylformide and chloroform as the solvents. X-ray diffraction and scanning electron microscopy with field emission gun were performed for CNs in order to determine its morphology and crystalline properties. The effect of non-isothermal crystallization of PHBV and its nanocomposites was studied using differential scanning calorimetry technique. The incorporation of CNs increases the crystallization rate with up to 3 wt%. Structural parameters were studied using positron annihilation lifetime spectroscopy and small-angle X-ray scattering. The free volume does not change upon CNs addition in spite of form less perfect crystals and increase the lamellar thickness. POLYM. COMPOS., 40:3156–3165, 2019. © 2018 Society of Plastics Engineers.